High long-term persistence to evolocumab treatment regimens in European clinical practice: analysis of the HEYMANS registry. (3rd October 2022) - Ray, K K; Perrone-Filardi, P; Ebenbichler, C; Vogt, A; Bridges, I; Sibartie, M; Dhalwani, N N
Abstract: Background: Lipid-lowering treatments (LLTs) require both adherence and persistence to the treatment regimen long-term to maximise treatment benefits. Small molecules require self-medication daily but therapies such as evolocumab are labelled for self-medication every 2 weeks or monthly. Limited data exist concerning the long-term persistence to evolocumab in routine clinical practice. Purpose: Using data from the HEYMANS registry, the objective of this analysis was to evaluate persistence and discontinuation of evolocumab in Europe. Methods: HEYMANS was a prospective registry including adults initiating evolocumab treatment in routine clinical practice in 12 European countries between August 2015 and June 2020. Originally designed to have up to 12 months of follow-up, the protocol was amended (February 2018) to extend follow-up for up to 30 months. Patients yet to complete 12 months follow-up at this date, were followed up for up to 30 months. Therefore, we analysed evolocumab discontinuation separately for the two time periods: 0–12 months (all), 12–30 months (subset). Results: Of the 1951 total patients, 30 patients discontinued participation in the study before 12 months (evolocumab use still ongoing at study discontinuation). Therefore, evolocumab use status was determined for 1921 patients at 12 months. Of these, 1781 (92.7%), remained on evolocumab at 12 months of follow-up (Figure). At 12 months, LDL-C levels were reduced from baseline by a median of 58% (Q1, Q3: 41%, 69%). In total, 1136 patients were eligible for extended follow up after protocol amendment. Of these, 137 patients discontinued study participation before 30 months of follow-up (with evolocumab ongoing). Therefore, evolocumab use status was determined in 999 patients, of whom, 92.2% (921) remained on evolocumab treatment at 30 months of follow-up (Figure). The reductions in LDL-C levels seen at 12 months were sustained throughout the study, with patients continuing to achieve median LDL-C reductions of 58% (Q1, Q3: 42%, 70%) from baseline at 30 months of follow-up. Conclusions: In this real-world study, representative of European practice, of patients who entered the extension phase, the proportion of patients who remained on evolocumab up to 30 months exceeded 90%, and treatment was associated with sustained LDL-C reductions. These data suggest that the self-administration regimen of evolocumab is both feasible and acceptable in general populations, providing long-term sustained, reductions in LDL-C with likely associated health benefits. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen (Europe) GmbH